The study of cardiotoxicity of hydroxychloroquine and azithromycine combination in hospitalized patients with COVID-19 - Yu. N. Belenkov; I. V. Menshikova; I. S. Ilgisonis; Yu. I. Naimann; Yu. V. Pak; I. R. Kolosova; A. S. Rakovskaya (Сеченовский вестник)
Hydroxychloroquine (HCH) is included in guidelines for treatment of novel coronavirus infection (COVID-19). Data on increased risk of cardiovascular complications when using it have been published. Aim. To evaluate the safety and tolerability of HCH and azithromycine (AZM) combination for the treatment of the patients with COVID-19 in recommended by Russian Ministry of Health doses in real practice.Methods. 132 patients (62 men and 70 women of average age 59.2 ± 9.3 years), 59% of whom had cardiovascular comorbidities, were included in prospective сohort study. 112 patients took HCH + AZM (group 1) and 20 patients took other medications without potential cardiotoxicity (group 2). At the admission to the hospital and after 5–7 days of the treatment corrected QT interval was calculated, new rhythm and conduction disorders, other side effects and hospital mortality have been registering. Relative risk (RR) and 95% confidence interval (CI) were calculated. Results. Elongation of corrected QT-interval within the normal range was registered in 22.3% of patients in group 1 and in 15% — in group 2. An increase in the QT length to the upper limit of the norm (480 msec) was observed in 1.8% of patients in group 1. There were no statistically significant differences between the groups in the number of patients with prolonged QT interval (RR = 1.488, 95% CI: 0.496–4.466, р = 0.478). The occurrence of new arrhythmias, conduction disturbances and allergic reactions was not recorded. Tolerability of combination HCH + AZM was satisfactory in the majority of patients. The hospital mortality in group 1 was 1.8%, in group 2 — 5% without statistically significant difference (p = 0.374). Conclusion. A combination of HCL + AZM according to the scheme recommended by the Ministry of Health of the Russian Federation for the treatment of the patients with COVID-19 and cardiovascular comorbidity in inpatient conditions is safe.